The phenotypic diversity in the production performance of Alabio ducks (Anas platyrhynchos Borneo) in South Kalimantan, Indonesia - Sulaiman, Abrani; Herliani, Herliani; Langai, Bambang; Parwanto, Parwanto; Surya, Rendra; Iqbal, Ahmad; Simanungkalit, Gamaliel (Journal of Advanced Veterinary and Animal Research, 2023)
Objective: This study aimed to examine the diversity of phenotypic characteristics of female Alabio ducks (Anas platyrhynchos Borneo) and their eggs in South Kalimantan, Indonesia. Materials and Methods: A total of 200 18-month-old ducks and 300 eggs were selected using a survey method with multistage random sampling. These samples were obtained from two districts in the province of South Kalimantan [Banjar (BJ) districts and Tanah Laut (TL)]. The observed data were analyzed descriptively with variations using the independent t-test for each location. Principal component analysis (PCA) was deployed to assess the overall variance and define variables with greater discriminatory power between individuals. Results: The observations on the body’s physical characteristics and the eggs of Alabio ducks showed significant differences between ducks from BJ and TL areas (p < 0.05) except for yolk diameter, albumen height, albumen index, and Haugh unit (HU) (p > 0.05). Most egg quality traits from BJ were greater than those from TL, which include egg weight, egg length, egg width, yolk weight, albumen weight, shell weight, shell thickness, and egg shape index. The PCA revealed medium-to high communalities in the phenotypic body characteristics of Alabio ducks and their eggs. Conclusion: Significant physical characteristics and egg quality differences were found between the two locations, except for the albumen index and HU, with substantial variability within each trait. These traits could explain the total variation in the phenotypic characteristics of female Alabio ducks. J. Adv. Vet. Anim. Res., 10(2): 249–256, June 2023 http://doi.org/10.5455/javar.2023.j676